Synthesis, In Silico and In Vitro Assessment of New Quinazolinones as Anticancer Agents via Potential AKT Inhibition - Ahmed A. Noser; Mohamed El-Naggar; Thoria Donia; Aboubakr H. Abdelmonsef (Molecules, 2020)
A series of novel quinazolinone derivatives (2–13) was synthesized and examined for their cytotoxicity to HepG2, MCF-7, and Caco-2 in an MTT assay. Among these derivatives, compounds 4 and 9 exhibited significant cytotoxic activity against Caco-2, HepG2, and MCF-7 cancer cells. Compound 4 had more significant inhibitory effects than compound 9 on Caco-2, HepG2, and MCF-7 cell lines, with IC50 values of 23.31 ± 0.09, 53.29 ± 0.25, and 72.22 ± 0.14µM, respectively. The AKT pathway is one of human cancer’s most often deregulated signals. AKT is also overexpressed in human cancers such as glioma, lung, breast, ovarian, gastric, and pancreas. A molecular docking study was performed to analyze the inhibitory action of newly synthetic quinazolinone derivatives against Homo sapiens AKT1 protein. Molecular docking simulations were found to be in accordance with in vitro studies, and hence supported the biological activity. The results suggested that compounds 4 and 9 could be used as drug candidates for cancer therapy via its potential inhibition of AKT1 as described by docking study.